The impact of welfare reform on marriage and divorce - Marianne P. Bitler; Jonah B. Gelbach; Hilary W. Hoynes; Madeline Zavodny (Federal Reserve Bank of Atlanta, 2002)
The goal of the 1996 Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA) was to end the dependency of needy parents on government benefits, in part by promoting marriage; the pre-reform welfare system was widely believed to discourage marriage because it primarily provided benefits to single mothers. However, welfare reform may have actually decreased the incentives to be married by giving women greater financial independence via the program's new emphasis on work. This paper uses Vital Statistics data on marriages and divorces during 1989-2000 to examine the role of welfare reform and other state-level variables on marriage and divorce rates. The results indicate that implementation of TANF is negatively associated with marriage and divorce rates, as are pre-TANF waivers from the AFDC program in some specifications.
Keywords: 330; Welfare